Self-Healing and Reprocessable Terpene Polysiloxane-Based Poly(thiourethane-urethane) Material with Reversible Thiourethane Bonds - Qian, Yuehan; Dong, Fuhao; Guo, Lizhen; Lu, Shanling; Xu, Xu; Liu, He (Biomacromolecules, 2023)
Polyurethane materials will come into contact with different solvents in daily life, and at the same time, they will be subject to different degrees of collision, wear and tear. Failure to take corresponding preventative or reparative measures will result in a waste of resources and an increase in costs. To this end, we prepared a novel polysiloxane with isobornyl acrylate and thiol groups as side groups, which was further used in the preparation of poly(thiourethane-urethane) materials. Thiourethane bonds generated by the click reaction of thiol groups with isocyanates endow poly(thiourethane-urethane) materials with the ability to heal and reprocess. Isobornyl acrylate with a large sterically hindered rigid ring promotes segment migration, accelerating the exchange of thiourethane bonds, which is beneficial to the recycling of materials. These results not only promote the development of terpene derivative-based polysiloxanes but also show the great potential of thiourethane as a dynamic covalent bond in the field of polymer reprocessing and healing.